Triple - Relational Latent Lexicology-phonology-semantic “mmrllexicolphonosemc” Analysis Model For Extracting Qura’nic Concept - Asma Abdul Rahman; Sarah Husna Mat Rasid (International Journal of Advanced Research in Islamic Studies and Education (ARISE), 2024)
Volume 2, Issue 1 (pages: 99-114)